Rheology of fluid and semisolid foods principles and applications - Rao, M. Anandha (New York Springer Science, 2007)
The second edition of this fascinating work takes readers from the basics right up to the complexities of this crucial topic area in food science. It examines the concepts needed to characterize
Keywords: Rheology; Food--Testing; Chemistry; Mechanics, Applied; Biotechnology; Mechanics; Food--Biotechnology